Effect of antioxidant agents on bond strength of composite to bleached enamel with 38% hydrogen peroxide - Silva, Juliane Marcela Guimaraes da [UNESP] (2011)
This study evaluated the effect of antioxidant agents on microtensile bond strengths (mTBS) of composite to bleached enamel. Fifteen freshly extracted human third molars were selected and randomly assigned to 6 groups (n = 5): (NB) enamel not bleached, (B) bleached enamel, (BR7) bleached enamel and restored 7 days later, (BSA) bleached enamel+sodium ascorbate, (BMC) bleached enamel+malvidin chloride, (BPC) bleached enamel+pelargonidin chloride. The groups were bleached with 38% hydrogen peroxide (HP - Opalescence Xtra Boost) and restored with Single Bond+Filtek Z350. The specimens were thermocycled and submitted to a microtensile load at 1 mm/min crosshead speed. The data were evaluated by ANOVA and Tukey test at 5% of significance. The mean and standard-deviation for all groups were: NB: 30.95(±11.97)a; BSA: 30.34(±8.73)a, BPC: 22.81(6.00)b, BR7: 21.41(±6.12)b, B: 14.10(±4.45)c, BMC: 13.25(±6.02)c. Sodium ascorbate reversed the bond strengths to enamel immediately after bleaching.